Vapor phase infiltration: from a bioinspired process to technologic application, a prospective review. (9th July 2018) - Azpitarte, Itxasne; Knez, Mato
Abstract: Abstract : Biomineralization is a natural concept to alter the mechanical properties of soft matter. Mimicking this concept became desirable with a resulting great variety of approaches toward realizing functional hybrid materials. Vapor-phase infiltration (VPI), a solvent-free approach, is complementary to solution-based processes and often provides hybrid materials with a different chemical nature. This article overviews the evolution of VPI from a curiosity-driven alternative way to mimic biomineralization toward its application in functional materials design. Even though still in infancy, the rapidly growing interest shows promise for upcoming innovative applications of VPI in a great variety of research and development directions.